PERANCANGAN APLIKASI MOBILE MAPPING LEMBAGA BIMBINGAN BELAJAR KOTA PADANG MENGGUNAKAN FRAMEWORK PHONEGAP - Erahayani Ritonga; Yasdinul Huda; Oktoria Oktoria (Universitas Negeri Padang, 2016)
Mobilephone is not only use as a device to send message or make a phonecall. manything that a smartphone can do, for example it can be use to look for some places or location such as courses. Padang, has some of courses for students. A large number of these courses are certainly not prospective for students who want to know. Based on this case, a solution that could fix this problem is by using digital mapping to help spreading the information about courses point place in Padang, with some fitures like news, or details about each of courses. Based on the case , this application is made to help spreading the information about courses point place in Padang, with some fitures like news, or details about each of courses. Based on the tittle this project has a client-server services, with a concept design using an UML. For implementation, this application is using PHP Programming language, HTML5, CSS3, and Javascript as editor and SDK Android Plugin, So it can be running in Eclipse Android Environment for helping user in using of it. Mobile Mapping Application is installed in Android Smartphone, so user can get the information easily about point place of courses in Padang. Keyword : Mobile Mapping, Phonegap, Android, Application, Client Server